Genome-Wide Association Study of Grain Architecture in Wild Wheat Aegilops tauschii - Arora, Sanu; Singh, Narinder; Kaur, Satinder; Bains, Navtej S.; Uauy, Cristobal; Poland, Jesse; Chhuneja, Parveen (Frontiers in Plant Science, 2017)
Aegilops tauschii, the D-genome progenitor of Triticum aestivum, encompasses huge diversity for various traits of potential economic importance such as yield, biotic and abiotic stress tolerance, quality and nutrition. In the present study, variation for grain size in Ae. tauschii germplasm was studied and its genetic basis dissected using genome wide association study (GWAS). Grain length, width and weight evaluated in 177 Ae. tauschii accessions over three years showed near normal distribution with 1.74, 1.75 and 2.82-fold variation, respectively. These lines were genetically characterized using Genotyping by sequencing (GBS) protocol that produced 11,489 single nucleotide polymorphic markers (SNP). Genetic diversity analysis revealed the presence of two distinct subgroups (designated as lineage 1 and 2) in Ae. tauschii. Based on GBS markers, the genetic similarity was calculated between the accessions and GWAS was conducted using 114 non-redundant accessions and 5,249 SNP markers. A total of 17 SNPs associated with grain size traits distributed over all the seven chromosomes were revealed with 6D, 5D and 2D harbouring most significant marker trait associations. Some of the chromosomal regions such as 6D_66.4 – 71.1 cM, 1D_143.5 – 156.7 cM and 2D_89.9 – 92.5 cM had associations with multiple traits. Candidate genes associated with cell division and differentiation were identified for some of the associated SNP markers. Further efforts to validate these loci will help to understand their role in determining grain size and allelic diversity in current germplasm and its effect on grain size upon transfer to bread wheat background.